Tall Farmers and Tiny Weavers. Rural Living Standards and Heights in Flanders, 1830-1870. - Depauw, Ewout (TSEG - The Low Countries Journal of Social and Economic History, 2018)
The evolution of the average stature of convicts between 1830 and 1870  in the prisons of Ghent and Bruges is used as a measure of the biological standard of living and suggests progress in the quality of life in the Flemish countryside, particularly for children born after 1850. Heights are used to shed light on regional variations. Prisoners born in coastal Flanders were on average shorter than inmates born in inland Flanders. Heights furthermore provide a key to discovering specific socio-economic differences that can explain such variations, showing that wage labourers in coastal Flanders and textile workers in inland Flanders were the shortest occupational groups, especially before 1850. As such, heights provide a nuanced picture of living standards in rural Flanders during the nineteenth century.